2008
DOI: 10.1111/j.1095-8649.2008.01906.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution patterns of fishes in a canyon‐shaped reservoir

Abstract: and 2005, an extensive study of the fish community was carried out in the largest water supply reservoir in the Czech Republic and Central Europe, the canyon-shaped Ž elivka Reservoir, using a fleet of Nordic multimesh gillnets. Fishes were sampled at eight locations along the longitudinal profile of the reservoir and at five benthic depth layers covering depths from the surface down to 18 m (benthic gillnet 1Á5 m high), and at three pelagic depth layers down to the depth of 5 m above the bottom (pelagic gilln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 75 publications
(113 reference statements)
4
49
0
3
Order By: Relevance
“…In artificially destratified, deep reservoirs fish inhabited the whole volume (Prchalová et al 2006). In the sharply stratified Římov Reservoir the highest fry density was usually observed in the surface layer as has also been observed for adult fish in other stratified lakes and reservoirs Järvalt et al 2005;Kahl & Radke 2006;Prchalová et al 2008).…”
Section: General Distribution Of Fry In the Reservoirsupporting
confidence: 71%
“…In artificially destratified, deep reservoirs fish inhabited the whole volume (Prchalová et al 2006). In the sharply stratified Římov Reservoir the highest fry density was usually observed in the surface layer as has also been observed for adult fish in other stratified lakes and reservoirs Järvalt et al 2005;Kahl & Radke 2006;Prchalová et al 2008).…”
Section: General Distribution Of Fry In the Reservoirsupporting
confidence: 71%
“…It was observed that, depending on a studied period, the inshore community was dominated by three fish species. The dominance of only a few highly abundant species was also observed by others investigators [11,32,52,56,65]. Decrease in the dominance of pikeperch was quite obvious (the average of its relative abundance dropped to 0.4% in period III compared to period I).…”
Section: Discussionsupporting
confidence: 55%
“…In contrast, several studies observed associations between abiotic variables and the distribution of the ichthyofauna in this type of environment (Oliveira et al 2005, Prchalová et al 2008. Some environmental variables are particularly associated with fish assemblages, such as depth (Prchalová et al 2008), availability of littoral zone food and shelter (Vidotto & Carvalho 2007), presence of aquatic vegetation (Pelicice et al 2005, Abes & Agostinho 2001, dissolved oxygen, temperature, pH, (Castro et al 2003, Araú jo et al 2009), transparency (Petry et al 2003) and conductivity (Rodríguez & Lewis 1997). Distribution and abundance patterns of fish species in reservoirs can also be affected by other physical habitat attributes, such as type and size of substrate, presence of macrophytes or submerged vegetation, and type and integrity of riparian vegetation (Kaufmann et al 2014).…”
Section: Discussionmentioning
confidence: 96%
“…Silva et al (2006) related low correlations between fish abundance and limnological characteristics to a low susceptibility of fish to alterations in limnological characteristics. In contrast, several studies observed associations between abiotic variables and the distribution of the ichthyofauna in this type of environment (Oliveira et al 2005, Prchalová et al 2008. Some environmental variables are particularly associated with fish assemblages, such as depth (Prchalová et al 2008), availability of littoral zone food and shelter (Vidotto & Carvalho 2007), presence of aquatic vegetation (Pelicice et al 2005, Abes & Agostinho 2001, dissolved oxygen, temperature, pH, (Castro et al 2003, Araú jo et al 2009), transparency (Petry et al 2003) and conductivity (Rodríguez & Lewis 1997).…”
Section: Discussionmentioning
confidence: 99%